Peran Pendidikan Agama Islam dalam Membangun Kecerdasan Emosional Remaja - Donna Takrim; Sandrina Ramadhani; Sri Juwita; Mardiah Astuti; Hartatiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) in developing adolescents’ emotional intelligence. In the modern era filled with social dynamics and moral challenges, emotional intelligence plays a crucial role in shaping a balanced personality that harmonizes intellect, emotion, and spirituality. Through PAI learning, Islamic values such as patience, empathy, self-control, and responsibility are instilled as the foundation for developing adolescents’ emotional intelligence. This research employs a descriptive qualitative approach using observation, interview, and documentation methods conducted in a school setting. The research subjects consist of Islamic Religious Education teachers and students at the secondary education level. The findings indicate that PAI plays a significant role in nurturing adolescents’ emotional intelligence through the internalization of moral values (akhlakul karimah), reflective activities, and the habituation of positive attitudes in daily life. Islamic Religious Education teachers serve as spiritual mentors and motivators who help students understand and manage their emotions in accordance with Islamic teachings. Therefore, PAI contributes strategically to shaping adolescents with strong character, self-control, empathy toward others, and a harmonious balance between intellectual and emotional intelligence.